Residual cardiovascular risk reduction guided by lifetime benefit estimation in patients with symptomatic atherosclerotic disease: effectiveness and cost-effectiveness. (2nd May 2021) - Hageman, Steven H J; Dorresteijn, Jannick A N; Bots, Michiel L; Asselbergs, Folkert W; Westerink, Jan; van der Meulen, Miriam P; Mosterd, Arend; Visseren, Frank L J; ,; Asselbergs, F W; Nathoe, H M; de Borst, G J; et al.
Abstract: Aims: To determine the (cost)-effectiveness of blood pressure lowering, lipid-lowering, and antithrombotic therapy guided by predicted lifetime benefit compared to risk factor levels in patients with symptomatic atherosclerotic disease. Methods and results : For all patients with symptomatic atherosclerotic disease in the UCC-SMART cohort (1996–2018; n  = 7697) two treatment strategies were compared. The lifetime benefit-guided strategy was based on individual estimation of gain in cardiovascular disease (CVD)-free life with the SMART-REACH model. In the risk factor-based strategy, all patients were treated the following: low-density lipoprotein cholesterol (LDL-c) < 1.8 mmol/L, systolic blood pressure <140 mmHg, and antithrombotic medication. Outcomes were evaluated for the total cohort using a microsimulation model. Effectiveness was evaluated as total gain in CVD-free life and events avoided, cost-effectiveness as incremental cost-effectivity ratio (ICER). In comparison to baseline treatment, treatment according to lifetime benefit would lead to an increase of 24 243 CVD-free life years [95% confidence interval (CI) 19 980–29 909] and would avoid 940 (95% CI 742–1140) events in the next 10 years. For risk-factor based treatment, this would be an increase of 18 564 CVD-free life years (95% CI 14 225–20 456) and decrease of 857 (95% CI 661–1057) events. The ICER of lifetime benefit-based treatment with a treatment threshold of ≥1 year additional CVD-free life per therapy was €15 092/QALY gained and of risk factor-based treatment €9933/QALY gained. In a direct comparison, lifetime benefit-based treatment compared to risk factor-based treatment results in 1871 additional QALYs for the price of €36 538/QALY gained. Conclusion : Residual risk reduction guided by lifetime benefit estimation results in more CVD-free life years and more CVD events avoided compared to the conventional risk factor-based strategy. Lifetime benefit-based treatment is an effective and potentially cost-effective strategy for reducing residual CVD risk in patients with clinical manifest vascular disease.